Blockchain Technology in Commerce: A Review of Its Applications in Supply Chain and Finance - Janhavi Shridhar Bedekar (AG Volumes, 2025)
With its exceptional efficiency, security, and transparency, blockchain technology is becoming one of the most revolutionary forces to have ever changed "supply chain management and finance". This article addressed the blockchain technology in commerce, blockchain for supply chains, role of blockchain in finance. This article concluded that blockchain technology is increasingly transforming supply chain management and financial services by enabling transparent, secure, and real-time transactions. While challenges related to scalability, interoperability, regulation, and sustainability persist, growing awareness and advancements in energy-efficient consensus, smart contracts, and IoT integration support wider adoption. With proper standards and regulatory support, blockchain can become a foundational technology in modern commerce.